PARADIGMA PENGELOLAAN KEUANGAN DAERAH SEBELUM DAN SELAMA PANDEMI COVID-19 DI KOTA KUPANG-NTT - Maria Droste Nini Soera; Nikson Tameno; Cicilia A. Tungga (RJABM (Research Journal of Accounting and Business Management), 2022)
ABSTRACT This study aims to determine the paradigm (point of view) of regional financial management before and during the Covid-19 pandemic in Kupang City based on regional financial management in 2018-2020.  To deal with the Covid-19 pandemic, the Government makes policies on the use of regional budgets which are then regulated in several regulations that have been passed.  This policy led to changes in the structure of the APBD due to the policy of refocusing and reallocating the budget.  This type of research is a comparative descriptive with a qualitative research approach.  Data collection techniques in this study were in the form of observation, interviews, and documentation.  Data analysis techniques in the form of data reduction, data presentation, and drawing conclusions.  There has been a change in the structure of the APBD, namely the PAD of Kupang City in 2020 decreased and the balancing funds from the center were diverted to deal with health problems due to Covid-19 in the City of Kupang such as DAK and DID.  Regional financial management is considered disobedient/compliance with the law but that is understandable.  Regional financial management in 2018 is categorized as effective and at the efficiency level it is categorized as efficient.  2019 is categorized as effective and quite efficient.  Meanwhile, 2020 is categorized as very effective and quite efficient.  The city government's transparency is assessed in accordance with the concept of transparency in regional financial management.   Keywords: Refocusing, Reallocation, Pandemic, Covid-19, APBD, Paradigm, Kupang City Government